Development of Fast Method to Upscaling Microbial Inoculums on Two Seedling Testplants - Pabar, Sándor Attila; Prettl, Nándor; Kotroczó, Zsolt; Biró, Borbála (Journal of Central European Green Innovation, 2023)
We investigated the effect of different microbial species on the germination and growth of white mustard (Sinapis alba L.) and perennial ryegrass (Lolium perenne L.), tested for two weeks. The experiment was carried out in a cell tray, filled with sandy soil:compost (9:1) mixture. The following microorganisms were used as treatment: Enterobacter ludwigii, Bacillus megaterium, B. subtilis, Kosakonia cowanii, Pseudomonas fluorescens Hx1 bacteria and Trichorderma harzianum T-22 microscopic fungi. After two weeks, we assessed the number of germinated mustard seeds, the wet and dry weight of the mustard, the length of the mustard, the wet and dry weight and the length of the ryegrass. We measured the enzyme activity of the fluorescein diacetate hydrolysis analysis (FDA) of the soils and calculated the correlation of FDA with the parameters, tested on seedling-plants. FDA generally was positively correlated, however, the above findings could not be verified statistically. The simple and relatively fast method can be suitable for the cost-effective pre-testing of different microbes and for the pre-selection of strains that can be used in further field tests.